2019
DOI: 10.1007/s42804-019-00031-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic inguinal exploration for impalpable undescended testis: can we avoid the open inguinal exploration altogether?

Abstract: Introduction Diagnostic laparoscopy is the gold standard for evaluating a child with impalpable undescended testis (UDT). During the diagnostic laparoscopy, if the vas and vessels are seen coursing through the inguinal canal, the standard norm is to explore the inguinal canal via an inguinal crease incision. In this study, however, we explored the feasibility of laparoscopic inguinal exploration without any additional inguinal crease incision. Materials and methods The prospective study was done from 1.1.2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Esposito et al ( 36 ) prefer laparoscopic inguinal exploration if the DIR is open, as the intraabdominal testis might have been migrated into the inguinal canal by the effect of abdominal insufflation, leaving exploration via the open surgery to patients with a closed DIR. In a more recent study, laparoscopic inguinal exploration was feasible in cases of impalpable UDTs, irrespective of the status of the DIR or the appearance of the testicular vessels; however, this study was limited by the small number of included cases ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…Esposito et al ( 36 ) prefer laparoscopic inguinal exploration if the DIR is open, as the intraabdominal testis might have been migrated into the inguinal canal by the effect of abdominal insufflation, leaving exploration via the open surgery to patients with a closed DIR. In a more recent study, laparoscopic inguinal exploration was feasible in cases of impalpable UDTs, irrespective of the status of the DIR or the appearance of the testicular vessels; however, this study was limited by the small number of included cases ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…The primary objective of surgery for NPT exploration is to determine the presence of viable testes, which can only be achieved by exposing the terminal end of the VDSV, with excision not adding significantly to the surgical time in such cases ( 31 ). On the other hand, considering the potential malignant precursor in atrophic nodules, most surgeons prefer excising the nodules during exploration, with laparoscopic inguinal exploration serving as a good alternative to open inguinal exploration ( 32 ). In line with our study, where laparoscopic exploration revealed blind-ended VDSV, we proceeded with inguinal exploration and excision of atrophic testicular nodules, whereas previous extensive research ( 1 , 5 , 6 , 15 ) classified this condition as testicular absence, thereby not exploring further.…”
Section: Discussionmentioning
confidence: 99%